PENGARUH PENDIDIKAN, UMP, INFLASI, DAN INVESTASI TERHADAP TINGKAT PENGANGGURAN DI INDONESIA - Sidabutar, Minar Adesima Rohayana; Putri, Novi Tri (Jurnal Cita Ekonomika, 2024)
This study aims to ascertain how Indonesia's open unemployment rate is affected by education, provincial minimum wage, inflation, and investment. The study's panel data, which covers the years 2020-2023, comes from 34 regions of Indonesia. The panel data, which combines cross-sectional and time series data, is analyzed using a quantitative descriptive approach. Secondary data were provided by the Central Bureau of Statistics. The Eviews 12 program was used in this work to conduct regression analysis on panel data using the Fixed Effect Model method. The research findings show that education, provincial minimum wage, inflation and investment statistically show a significant negative impact on the unemployment rate in Indonesia. The implications for policy include the need for UMP policies that are in line with local economic conditions, improving education as an investment in human resources, managing inflation, and the importance of attracting domestic and foreign investment to encourage economic expansion and reduce unemployment.